Concrete Canoe / Mohamad Shamsul Izwan Sukeri ... [et al.] - Sukeri, Mohamad Shamsul Izwan; Ahmad Termidi, Nur Syarhana; Shubri, Siti Najwa; Shikh Nasir, Siti Norhayati; Bakar, M. Riduwan; Mustafa, M. Nazwan; Alisibramulisi, Anizahyati; Mohd Amin, Norliyati (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
Nowadays, lightweight concrete, also known as EPScrete (expanded polystyrene concrete), is a material widely used in the building of environmentally green homes. That was how the idea of creating concrete canoe as an alternative application of the EPScrete came. The EPScrete consisted of polystyrene, sand cement and water. Expanded polystyrene beads are non-absorbent, easily compressible and their direct contribution to the compressive strength of the concrete is negligible. Due to its porosity and buoyancy, this lightweight concrete can float on the water. The advantages of this floating concrete structure are it reduces mass and improves thermal while maintaining adequate strength, resulting in overall cost reduction. Hopefully, this concrete canoe can be beneficial to villagers as an alternative transportation.